Quiz 2.4

Quiz 2.4 - 1)...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon
1 ) Use the Chain Rule to compute the derivative for #2 and simplify  your answer. (5pts)   y' = 4(1 - x^2) - 1   y' = 4x - 1   y' = 8x^3 + 6x   y' = 8(1 - x^2)^3 + 6(1 - x^2) 2 ) Differentiate #24. (5pts)   f'(s) = (5s^3 + 2)(15s^2)^(-3/2)   f'(s) = (-15/2)s^2(5s^3 + 2)^(-3/2)   f'(s) = (-1/2)(15s^2)^(-3/2)   f'(s) = (5s^3 + 2)(15s^2)^(-3/2) Answer : Corre ct Points: 5 3 ) Differentiate #22. (5pts)   f'(x) = (12x + 5)(6x^2 + 5x + 1)^-3   f'(x) = (-48x - 20)(6x^2 + 5x + 1)^-3   f'(x) = -4(12x + 5)^-3   f'(x) = (6x^2 + 5x + 1)(12x + 5)^-3 Answer : Incorrec t Points: 0 4 )
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Differentiate #18. (5pts)   f'(x) = (30x^5)(5x^6-12)^(-1/2)   f'(x) = (15x^5)(5x^6-12)^(-1/2)   f'(x) = (5x^6 - 12)(30x^5)^(-1/2)   f'(x) = (1/2)(30x^5)^(-1/2) Answer : Incorrec t Points: 0 5 ) Differentiate #26. (5pts)
Background image of page 2
Image of page 3
This is the end of the preview. Sign up to access the rest of the document.

Page1 / 5

Quiz 2.4 - 1)...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online